INHERITANCE AS A BASIS FOR THE ACQUISITION OF OWNERSHIP RIGHTS OVER REAL ESTATE AND AGRICULTURAL LAND BY FOREIGN CITIZENS - Krstinić, Dalibor; Zarubica, Sara; Matijašević, Jelena; Bingulac, Nenad; Dragojlović, Joko (Economics of Agriculture, 2024)
The subject of research in the paper will be the right of foreign citizens to inherit real estate and agricultural land in the Republic of Serbia. By using the methodologicaltheoretical framework, the aim of the work will be the analysis of the inheritance institute, which represents the basis of acquisition of property rights on real estate and agricultural land by foreign citizens. The era of globalization favors the movement of people between countries, but each country determines the availability and scope of rights of foreign nationals according to its interests. Therefore, in order to analyze the research subject, we will use historical, descriptive, normative and content analysis methods. The conclusion will summarize the results of research on inheritance as a basis for acquiring property rights on real estate and agricultural land by foreign citizens.rights over real estate and agricultural land by foreign citizens.